Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3109/09546634.2012.715240
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine/tetracaine peel in topical anesthesia prior to laser-assisted hair removal: Phase-II and Phase-III study results

Abstract: After a 30-min application, LT peel was effective and well-tolerated in providing anesthesia for laser-assisted hair removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…As LT cream forms a self‐occlusive film when exposed to air, it is said to not require plastic occlusion. LT cream has shown superiority over placebo in pain reduction during several dermatological laser procedures, and lower pain scores compared with LP cream during (superficial) single‐pass CO 2 laser skin resurfacing . However, apart from this single study, no head‐to‐head studies have been performed for other dermatological indications or laser systems.…”
mentioning
confidence: 99%
“…As LT cream forms a self‐occlusive film when exposed to air, it is said to not require plastic occlusion. LT cream has shown superiority over placebo in pain reduction during several dermatological laser procedures, and lower pain scores compared with LP cream during (superficial) single‐pass CO 2 laser skin resurfacing . However, apart from this single study, no head‐to‐head studies have been performed for other dermatological indications or laser systems.…”
mentioning
confidence: 99%
“…on the effect of lidocaine/tetracaine (LT) peel in topical anesthesia prior to laser-assisted hair removal, the results showed that VAS scores were significantly lower for LT peel (26.7 for LT peel vs. 44.3 for placebo), and for that study and ours, subjects’/investigators’ ratings favored LT peel were evaluated which are in accordance. [13] Therefore, the combination of lidocaine 7% and tetracaine 7% provides rapid anesthesia onset with minimal side effects, and could be a practical alternative for older local anesthetic agents used before laser-assisted hair removal and also improves patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Average application dose ranges from 0.9 to 1.7 g/10 cm 2 . Studies also demonstrate that application on an area up to 400 cm 2 for as long as 120 min produced a maximum peak plasma lidocaine concentration of 0.220 μg/mL, which is far below the lower toxic limits of lidocaine [33].…”
Section: Novel Lidocaine/tetracaine Formulationsmentioning
confidence: 97%
“…The product incorporates lidocaine 7 % and tetracaine 7 % (Pliaglis, Galderma, SA) providing fast and prolonged relief during dermatologic procedures [33]. The self-occluding, air-drying agent is applied to involved skin and easily peels off after only 30 min.…”
Section: Novel Lidocaine/tetracaine Formulationsmentioning
confidence: 99%